2021
DOI: 10.3390/su13052577
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory Exploration of Language Massive Open Online Courses (LMOOCs): Understanding Students’ Viewpoints

Abstract: Massive open online courses (MOOCs) have been called the biggest innovation in education in 200 years for their unique attribute of being open and free to any individual with Internet access; however, their high dropout rate has led many people to be concerned or dubious about their effectiveness and applicability. The applicability of MOOCs in English for specific purposes (ESP) courses (in this case, hospitality English) needs more empirical evidence; the present study intends to help fill this gap and exten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…Prior studies have identified multiple reasons that individuals abandon MOOCs as their learning modality ( Dai, Teo, & Rappa, 2020 ; Reparaz, Aznárez-Sanado, & Mendoza, 2020 ; Wei et al, 2020 ; Hsu, 2021 ). The low terminal completion rates of MOOCs indicate that there is a lack of self-regulation and self-motivation compared with what is expected from the students ( Dai et al, 2020 ; Wei et al, 2020 ; Moore & Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified multiple reasons that individuals abandon MOOCs as their learning modality ( Dai, Teo, & Rappa, 2020 ; Reparaz, Aznárez-Sanado, & Mendoza, 2020 ; Wei et al, 2020 ; Hsu, 2021 ). The low terminal completion rates of MOOCs indicate that there is a lack of self-regulation and self-motivation compared with what is expected from the students ( Dai et al, 2020 ; Wei et al, 2020 ; Moore & Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another example, using roundtable discussion sessions was found to be a good way to identify areas of agreement and disagreement, especially when the topic involves multiple persons with different backgrounds (Shen, 2021) and requires embracement of broad differences in LMOOCs (Mac Lochlainn et al, 2020). This study also identified concrete teaching practices to show how to provide more flexible options in a large-scale LMOOC that take account of learners' linguistic, cultural, psychological and cognitive difference (Read & Barcena, 2021), thus making a direct response to a recent call in LMOOC research regarding the individualization of teaching contents (e.g., Chong et al, 2022;Hsu, 2021a;Jitpaisarnwattana et al, 2021b;Jitpaisarnwattana et al, 2022b;Mac Lochlainn et al, 2021;Martín-Monje et al, 2018;Nie & Hu, 2018). However, at the same time, the authors found little use of innovative activities in teaching presence, such as the use of online games, vocabulary contests, and/or live chat rooms, as proposed by previous LMOOC studies (Friðriksdóttir, 2021a;Hsu, 2021b;Yaşar, 2020;Zhao, 2015).…”
Section: Identified Exemplary Practices In Lmoocs and Implications Fo...mentioning
confidence: 85%
“…As for course design and teaching, major challenges include: (a) Course design and instruction both need to be more structured and professional (Friðriksdóttir, 2021a;Jitpaisarnwattana et al, 2022c;Nie & Hu, 2018;Zhao, 2015), (b)The current LMOOCs need to integrate rich, innovative, and engaging activities, such as online games, vocabulary contests, and/or live chat rooms (Friðriksdóttir, 2021a;Hsu, 2021b;Yaşar, 2020;Zhao, 2015), (c) The teaching materials need to be more closely connected to students, and allow individualized pathways to learning (Chong et al, 2022;Hsu, 2021a;Jitpaisarnwattana et al, 2021b;Jitpaisarnwattana et al, 2022b;Mac Lochlainn et al, 2021;Martín-Monje et al, 2018;Nie & Hu, 2018), and (d) A lack of teaching presence (Jitpaisarnwattana et al, 2022c).…”
Section: The Embodiment Of Coi In Lmoocsmentioning
confidence: 99%
“…General satisfaction, positive evaluation [39] Grammar Undergraduates in Saudi Arabia Mixed [40] Language and literature K-12 students in the US Mixed [41] English for Specific Purpose Hospitality English Learners in China Positive, helpful [42] Agriculture and forestry English Graduates in China Effective, meaningful [43] Maritime English College students in China Positive [44] Overall English skills…”
Section: Adult Learners In South Koreamentioning
confidence: 99%
“…The advantages of learning a language online were acknowledged. The affordance, flexibility, convenient retrieval, and interaction observations of MOOCs were highly praised by hospitality English learners because information about the subject can be retrieved any-time, anywhere, without disappearing [42]. Spatial and temporal convenience, self-paced learning, and one-to-one feedback were considered the major advantages of online learning when trainees learn English translation and interpreting online.…”
Section: Practical Implicationsmentioning
confidence: 99%